"Why Are You Here? Can't You Cope at Home?" The Psychiatric Crisis of People With Intellectual Disabilities and the Community's Response. Issue 2 (3rd April 2017) - Spassiani, Natasha; Abou Chacra, Megan Sarah; Lunsky, Yona
ABSTRACT: Introduction : Individuals with intellectual disability (ID) are high users of emergency mental health services and can experience stigmatization in these circumstances. The purpose of the study was to examine the experiences of people with ID living in the community who interact with emergency services as a result of a psychiatric crisis, from the perspective of individuals with ID and their caregivers. Methods : In this qualitative study, we interviewed 12 individuals with ID, four family members and five direct support staff who visited emergency departments (EDs) during psychiatric crises. Thematic analyses were conducted on interview transcripts. Results : Four themes emerged: ID and mental health stigma, stigma preventing people from accessing services, lack of support, and concern regarding care planning. Participants reported feeling either dismissed or disrespected by emergency personnel, that staff are ill-prepared to support this population, and that they experience poor transitions between hospital and community. Conclusions : Work needs to be done to reduce stigma experienced by those with ID and mental health issues when using emergency services. Education and training should target individuals, caregivers, community providers, and emergency personnel.